Time effects in evolution of structure and rheology of highly concentrated emulsions - Kharatiyan, Ellina (Cape Peninsula University of Technology, 2016)
Thesis (DTech (Chemical Engineering))--Cape Peninsula University of Technology, 2005. === The subject of this study is highly concentrated emulsion explosive (HCEE). These emulsions are dispersions of an aqueous phase (up to 90 v-%) in an oil phase. The dispersed droplets consist of an aqueous solution of nitrate salts, which is supersaturated at room temperature, comprising less than 20% of water by mass. Compounds of this kind are thermodynamically unstable and their instability is related to the coarsening of emulsion (coalescence) and phase transition (crystallization) of dispersed phase. However it is demonstrated that the dominating mechanism is slow crystallization inside the super-cooled droplets. The main goal of this thesis is a phenomenological study of the dependence of structural parameters, such as droplet size and volume fraction, as well as the ageing processes, on the rheological properties of these emulsions. The results of the measurements include the flow and viscoelastic properties of the materials. The rheological parameters are correlated with the kinetics of structural changes during ageing, as a function of emulsion formulation. The emulsions under study are non-Newtonian liquids. Experiments in shear rate sweep mode demonstrate that the upward and downward branches of the flow curves coincide above some specific shear rate value. The upward experiments show the existence of a low shear Newtonian asymptote, while the effect of yielding is observed in the downward curve. Wall slip is investigated and shown to be negligible.